The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/jcpe.13103
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic assessment after root coverage of multiple adjacent recessions with coronally advanced flap with adjunctive collagen matrix or connective tissue graft: Randomized clinical trial

Abstract: Background Few studies have looked at professional assessment or patient perception of aesthetics after root coverage procedures. The addition of connective tissue grafts (CTG) seems to improve aesthetic outcomes. The objective of this a priori analysis was to compare aesthetics after addition of CTG or a collagen matrix (CMX) to coronally advanced flap (CAF). Methods Two independent, trained and calibrated assessors analysed baseline and 6‐month post‐operative Images from 183 subjects with 475 recessions from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 21 publications
(49 reference statements)
1
8
1
8
Order By: Relevance
“…The results of the present report together with the previous ones (Tonetti et al, 2018; Pelekos et al, 2019) of this trial show improved root coverage outcomes for both test and control treatments. Interpretation of the inter‐group difference is affected by the loss of power arising from the fact that only 8 study centres were available for the 3‐year follow‐up.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The results of the present report together with the previous ones (Tonetti et al, 2018; Pelekos et al, 2019) of this trial show improved root coverage outcomes for both test and control treatments. Interpretation of the inter‐group difference is affected by the loss of power arising from the fact that only 8 study centres were available for the 3‐year follow‐up.…”
Section: Discussionsupporting
confidence: 84%
“…They confirm that application of CTG combined with a specifically designed CAF is probably the best approach for root coverage at multiple adjacent recessions (Tonetti et al, 2018). Use of a CMX, and avoidance of a CTG donor site, results in shorter time to recovery, less post‐operative morbidity (Tonetti et al, 2018) and more natural tissue texture and contour (Pelekos et al, 2019). CTG or CMX results in similar stability of outcomes between 6 and 36 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study evaluated the aesthetic outcomes from a multicenter randomized clinical trial comparing CAF + CTG versus CAF + XCM (Pelekos et al., 2019). Although CTG achieved an overall higher RES than XCM, the authors reported superior scores with XCM for STT and MTC (Pelekos et al., 2019). In line with this study, we observed that CAF + GS (either XCM or ADM) obtained better MTC than CAF alone.…”
Section: Discussionmentioning
confidence: 99%
“…This aspect needs to be kept in mind since emerging evidence suggests that CTG should not be considered as the panacea for the treatment of gingival recessions, since similar root coverage outcomes can be obtained with flap alone in the presence of a thick gingival phenotype (Cairo et al., 2020). A cost‐effective evaluation should be performed for each patient to decide the best treatment option considering the clinical, aesthetic‐ and patient‐related outcomes (Pelekos et al., 2019). Patients’ psychosocial factors, such as anxiety, depression, stress and well‐being, should also be take into account as they can affect the overall perception of the procedure, post‐surgical morbidity and medication consumption (Kloostra, Eber, Wang, & Inglehart, 2006).…”
Section: Discussionmentioning
confidence: 99%